2014
DOI: 10.1021/am504147q
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of Electro-oxidation Catalysis by Bulk-Structural Transformation in Intermetallic ZrPt3 Nanoparticles

Abstract: Although compositional tuning of metal nanoparticles (NPs) has been extensively investigated, possible control of the catalytic performance through bulk-structure tuning is surprisingly overlooked. Here we report that the bulk structure of intermetallic ZrPt3 NPs can be engineered by controlled annealing and their catalytic performance is significantly enhanced as the result of bulk-structural transformation. Chemical reduction of organometallic precursors yielded the desired ZrPt3 NPs with a cubic FCC-type st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 42 publications
(46 reference statements)
2
30
0
Order By: Relevance
“…Hideki et al found that both 150-nm NbPt 3 and 100-nm TaPt 3 intermetallic particles showed significant enhancement in catalytic activity and stability compared with Pt NPs 31,32 . Despite these obvious advantages, the works of the related early transition metal nano-intermetallic compounds are preliminary (e.g., Pt 3 Ti 28,29 , Pt 3 V 29 , ZrPt 3 30 , NbPt 3 31 , TaPt 3 32 , and Pt 3 Y 33 ) due to higher melting points, more oxyphilic nature and much more negative reduction potentials of these metals compared with late transition metals. Furthermore, non-precious early transition metal nano-intermetallics, to the best of our knowledge, have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Hideki et al found that both 150-nm NbPt 3 and 100-nm TaPt 3 intermetallic particles showed significant enhancement in catalytic activity and stability compared with Pt NPs 31,32 . Despite these obvious advantages, the works of the related early transition metal nano-intermetallic compounds are preliminary (e.g., Pt 3 Ti 28,29 , Pt 3 V 29 , ZrPt 3 30 , NbPt 3 31 , TaPt 3 32 , and Pt 3 Y 33 ) due to higher melting points, more oxyphilic nature and much more negative reduction potentials of these metals compared with late transition metals. Furthermore, non-precious early transition metal nano-intermetallics, to the best of our knowledge, have not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…54 mg of Vulcan carbon was added to the reaction mixture. The reaction mixture was then transferred to a stainless-steel pressure vessel and heated at 200°C in an oil bath for 2 h under an argon pressure of 0.5 MPa [34,35]. The product was then transferred to a centrifuge tube under an argon atmosphere.…”
Section: Synthesis Of Pd 3 Ti/c Npsmentioning
confidence: 99%
“…Then, 30 ml of diglyme were added to the vessel, and the mixture was stirred for 20 min to dissolve the reactants. Next, 1 ml of super-hydride was added to the reaction mixture, which was heated at 200°C in an oil bath for 2 h under an argon pressure of 0.5 MPa [34,35]. The product was then transferred to a centrifuge tube under an argon atmosphere.…”
Section: Synthesis Of Pd 3 Zr/c Npsmentioning
confidence: 99%
See 1 more Smart Citation
“…PtCo, PtFe, PtCu, and PtCr. [20][21][22][23][24][25][26][27][28] Recently, ternary nanoparticles have gained growing attention as promising catalysts to enhance catalytic performances by providing more possibilities to modify the crystal phase of existing PtM catalysts. [29][30][31][32][33] Introducing third metal elements to the present binary catalysts for catalytic materials has been used to achieve superior catalytic performances.…”
Section: Introductionmentioning
confidence: 99%